Functions of Tfh Cells in Common Variable Immunodeficiency - Le Saos-Patrinos, Corentin; Loizon, Séverine; Blanco, Patrick; Viallard, Jean-François; Duluc, Dorothée (Frontiers in Immunology, 2020)
Common variable immunodeficiency is the most common clinical primary immunodeficiency in adults. Its hallmarks are hypogammaglobulinemia and compromised B-cell differentiation into memory or antibody-secreting cells leading to recurrent infections. This disease is heterogeneous, with some patients harboring multiple complications such as lymphoproliferative disorders, autoimmune manifestations or granulomatous inflammation. The mechanisms leading to these complications remain elusive despite numerous associations found in the literature. For instance, although described as a B cell intrinsic disease, numerous abnormalities have been reported in other immune cell compartments. Here, we tuned our attention to follicular helper T cells, a CD4+ T cell population specialized in B cell help, considering the recent publications showing an involvement of these cells in CVID pathogenesis.